Sharing the joy celebrating Eid Ul Ftri - Siti Sarah, Mohamad Rajimi (2017)
Nothing is much happier than to see the smile on the faces of these orphans, asnaf and the disabled when they were given the opportunity to shop for Aidilfitri at Mydin Hypermarket in Kuantan.